(untitled) (Window of Public Health Journal, 2026)
According to World Health Organization (WHO) data, approximately 12 million pregnant women worldwide experience health problems in the third trimester, with approximately 30% experiencing anxiety related to childbirth. Anxiety in pregnant women can negatively impact the condition of both the mother and the fetus. This study aims to present findings on key determinants of pregnancy-related anxiety among third-trimester pregnant women in the working area of ​​the Kaluku Bodoa Community Health Center, Makassar City. This study used a quantitative design with a cross-sectional approach. The study sample consisted of 85 third-trimester pregnant women selected from the working area of ​​the Kaluku Bodoa Community Health Center. Data were collected using a structured questionnaire and analyzed statistically to determine the relationship between variables. The results showed a significant influence between parity (p=0.002), economic status (p=0.005), history of miscarriage (p=0.011), history of domestic violence (p=0.000), and husband’s support (p=0.000) on the level of anxiety in third-trimester pregnant women. In conclusion, reproductive factors, socioeconomic status, obstetric experience, psychosocial conditions, and family support play a significant role in determining a pregnant woman’s anxiety levels. Therefore, pregnant women are advised to actively seek information related to pregnancy and childbirth and to be open with healthcare providers about their emotional experiences to help reduce anxiety levels.